A simplified online adaptive workflow for long-course magnetic resonance-guided radiotherapy in esophageal cancer - Koen M. Kuijer; Roel Bouwmans; Lando S. Bosma; Stella Mook; Gert J. Meijer (Physics and Imaging in Radiation Oncology)
Background and Purpose: Online adaptive magnetic resonance-guided radiotherapy (MRgRT) enables high-precision radiotherapy for esophageal cancer patients but is less feasible due to long on-table times in combination with long-course treatment. In this study, we conducted an in-silico assessment of a simplified online adaptive workflow, Adapt-To-Shape-lite (ATS-lite), in which deformable propagated contours are not modified, and assessed its feasibility. Materials and Methods: The ATS-lite workflow was simulated for all fractions of nine esophageal cancer patients who had previously received full online adaptive MRgRT with manual contour corrections if needed. The deformable propagated contours were not adjusted. A dose of 41.4 Gy in 23 fractions was prescribed. Intra- and interfraction dose accumulation were performed to evaluate target coverage per fraction and across the entire treatment. For individual fractions, coverage of the manually corrected clinical target volume (CTV) was considered adequate if V95% > 98 % and V90% > 99.5 %. Feasibility was assessed by recording treatment times in the first patients treated with ATS-lite. Results: The ATS-lite workflow provided adequate target coverage over the entire treatment for all patients, with sufficient coverage in 90% of the 177 fractions analyzed. Closer inspection revealed that inadequate target coverage in individual fractions was primarily attributed to enlargement of the manually corrected CTV, rather than poor contour propagation in the ATS-lite workflow. In seven patients, the ATS-lite workflow achieved a median time per fraction of 23 min. Conclusions: The ATS-lite workflow provides adequate target coverage and is feasible for online adaptive MRgRT in long-course esophageal cancer treatments.